METHODS OF DETERMINING EXPERIMENTAL SKILLS IN GENERAL PHYSICS PRACTICE (Scientific journal of the Fergana State University, 2024)
Development of experimental skills, increasing the effectiveness of physics practical classes, enriching the content of laboratory practice, evaluating students' theoretical knowledge, skills and qualification, involving students in experimental assignments.